DES study of blade trailing edge cutback cooling performance with various lip thicknesses. (25th April 2016) - Effendy, M.; Yao, Y.F.; Yao, J.; Marchant, D.R.
Highlights: Detached-eddy simulation of the mixing process between mainstream flow and coolant Effects of various t/H ratios on blade trailing-edge cutback cooling performance. Vortex shedding behind the lip plays an important role in near wall cooling efficiency. Discharge coefficient and adiabatic film-cooling effectiveness agree with experiment. Thermal mixing has been greatly intensified with the increase of the t/H ratio. Abstract: Three-dimensional detached-eddy simulation (DES) study has been carried out to evaluate the cooling performance of a trailing-edge cutback turbine blade with various lip thickness to slot height ratios ( t/H ). By adopting the shear-stress transport (SST) k-ω turbulence model, the numerical investigations were performed at two successive steps: first, to validate simulation results from an existing cutback turbine blade model with staggered circular pin-fins arrays inside the cooling passage against experimental measurements and other available numerical predictions; second, to understand the effects of the lip thickness to the slot height ratio on the blade trailing-edge cooling performance. It was found from the model validations that at two moderate blowing ratios of 0.5 and 1.1, DES predicted film cooling effectiveness are in very good agreement with experimental data. Further comparisons of four various t/H ratios ( t/H = 0.25, 0.5, 1.0, 1.5) have revealed that the thermal mixing process between the 'cold' coolant gas and the 'hot' mainstream flow in the near wake region of the exit slot has been greatly intensified with the increase of the t/H ratio. As a result, it causes a rapid decay of the adiabatic film cooling effectiveness downstream of the blade trailing-edge. The observed vortex shedding and its characteristics in the near wake region are found to play an important role in determining the dynamic process of the 'cold' and the 'warm' airflow mixing, which in turn have significant influences on the prediction accuracy of the near-wall heat transfer performance. As the four t/H ratio increases from 0.25 to 1.5, DES predicts the decrease of main shedding frequencies as fs = 3.69, 3.2, 2.21, and 1.49 kHz, corresponding to Strouhal numbers St = 0.15, 0.20, 0.23, and 0.22, respectively. These results are in good agreement with available experimental measurements.